Keterbukaan Informasi Publik di Kabupaten Lebak - Hidayat, Hidayat (Badan Strategi Kebijakan Hukum dan HAM, 2010)
The objective of the research on the Rights of Freedom to Public Information Government Held is to determine the readiness of the Government of Lebak Regency in implementing the Act. 14 Year on year 2008 and factors inhibiting the implementation. The study was conducted with qualitative methods through descriptive analysis approach. The results of the research shows that the Government Lebak Regency basically ready to implement the Law Number 14 Year 2008 concerning Public Information Disclosure Regulation by enacting Local Regulation No. 6 of 2004 on Transparency and Participation in Governance and Development Management at the Commission Lebak Regency establishment of Transparency and Participation can accommodate the aspirations of the community in order to obtain information.